A proof with a mistake ( or not ) Part 2

The Leibniz formula for π \pi states that 1 1 3 + 1 5 1 7 . . . . . . . = π 4 1 - \frac{1}{3} + \frac{1}{5} - \frac{1}{7} ....... = \frac{\pi}{4} or 4 ( 1 1 3 + 1 5 1 7 . . . . . . . ) = π . 4\left(1 - \frac{1}{3} + \frac{1}{5} - \frac{1}{7} ....... \right) = \pi . The following procedure uses the Lebniz formula to prove that π = 4. \pi=4. Find the incorrect step.

Step 1 - Termwise, add 4 ( 1 3 1 5 + 1 7 . . . . . . . ) 4\left( \frac{1}{3} - \frac{1}{5} + \frac{1}{7} .......\right) to the LHS of the formula, and then subtract it at the end again, to keep the value constant at π \pi . Doing so, we get 4 ( 1 + 1 3 1 3 + 1 5 1 5 . . . . . . . . ) 4 ( 1 3 1 5 + 1 7 . . . . . . . ) = π 4\left( 1 + \frac{1}{3} - \frac{1}{3} + \frac{1}{5} - \frac{1}{5} ........\right) - 4\left( \frac{1}{3} - \frac{1}{5} + \frac{1}{7} .......\right) = \pi

Step 2 - We can see that 1 3 1 5 + 1 7 . . . . . . . = ( π 4 1 ) , \frac{1}{3} - \frac{1}{5} + \frac{1}{7} ....... = -\left(\frac{\pi}{4} - 1\right) , so 4 ( 1 ) ( ( π 4 1 ) = π 4(1) -(-(\frac{\pi}{4} - 1) = \pi

Step 3 - Simplifying,we get ( 4 1 + π 4 ) = π (4 - 1 + \frac{\pi}{4}) = \pi We subtract π 4 \frac{\pi}{4} from both sides to obtain 3 = 3 π 4 3 = \frac{3\pi}{4} But this means that π = 4 \pi = 4 !

Step 1 Step 3 There is no mistake and π = 4 \pi = 4 Step 2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Tan Li Xuan
May 6, 2014

The problem is in the second step.The fact that 1 3 1 5 + 1 7 . . . . . . . = ( π 4 1 ) \frac{1}{3} - \frac{1}{5} + \frac{1}{7} ....... = -(\frac{\pi}{4} - 1) is true,however it should have been multiplied by 4 because the original expression was 4 ( 1 3 1 5 + 1 7 . . . . . . . ) 4(\frac{1}{3} - \frac{1}{5} + \frac{1}{7} .......) so it should be 4 ( 1 ) 4 ( ( π 4 1 ) ) 4(1) - 4(-(\frac{\pi}{4} - 1))

Wow, I must admire you have brilliant posted a problem that really is convincingly true. For the first time I was pretty confused like "Hey, man, I studied math for this many years and this guy suddenly comes upfront saying that π = 4 \pi = 4 ?" Truly magnificent.

Umang Vasani - 7 years ago

Log in to reply

Thanks :) I actually came up with this in a weird way.When I have free time during class,I try and solve some problems on a piece of paper.I just happened to come up with this and I found the mistake while I was proofreading it.

Tan Li Xuan - 7 years ago
Anand Raj
Jun 23, 2014

4 should be common to both not only 1

that was a good question.It need a concentrated observation

4 is missing in step 2.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...